1998
DOI: 10.1038/sj.onc.1202071
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-mediated protection from drug cytotoxicity: association with p21WAF1/CIP1 protein accumulation?

Abstract: Dexamethasone (DEX)-mediated inhibition of druginduced, but not CD95 ligand-induced, apoptosis in malignant glioma cells correlates with wild-type p53 status. Here, we examined mechanisms underlying DEXmediated protection from apoptosis. DEX did not induce p53 expression in two p53 wild-type cell lines (U87MG, LN-229) and did not alter drug-induced p53 accumulation. human colon carcinoma cells. Paradoxically, while only p21 +/+ and p21 +/7 mouse embryonic ®broblasts showed enhance p21 WAF1/CIP1 levels after ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 24 publications
1
44
2
1
Order By: Relevance
“…2) and LN-229 cells (data not shown) with the murine temperaturesensitive p53 V135A mutant, which acts as a dominantnegative mutant at 38.5°C. 4,5 Expression of p53 V135A was confirmed by immunoblot using antibody pAb 240, which has as very low reactivity with the endogenous p53 protein in human glioma cell lines ( Fig. 2A).…”
Section: Inhibition Of Proliferation By Acidosis: the Role Of P53mentioning
confidence: 96%
See 2 more Smart Citations
“…2) and LN-229 cells (data not shown) with the murine temperaturesensitive p53 V135A mutant, which acts as a dominantnegative mutant at 38.5°C. 4,5 Expression of p53 V135A was confirmed by immunoblot using antibody pAb 240, which has as very low reactivity with the endogenous p53 protein in human glioma cell lines ( Fig. 2A).…”
Section: Inhibition Of Proliferation By Acidosis: the Role Of P53mentioning
confidence: 96%
“…U87MG and LN-229 expressing murine temperature-sensitive p53 V135A cells were described previously. 4,5 Transgene expression was assessed by immunoblot analysis. 4 The cells were cultured in Dulbecco modified Eagle medium containing 5% fetal calf serum and penicillin (100 IU/mL)/streptomycin (100 g/mL).…”
Section: Materials and Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids were found to enhance the cytotoxicity of cisplatin via suppression of NF-κB activation in the GR-rich human cervical carcinoma cell line SiHa [88,89]. On the other hand, other studies have shown that glucocorticoids decrease the chemosensitivity in non-hematological solid tumors cells through a variety of mechanisms, which include the modulation of bcl-x gene expression, and the up-regulation of p21 Cip1 and mitogenactivated protein kinase phosphatase-1 (MKP-1) [22,97,159].…”
Section: Pre-clinical and Clinical Trials Of Nf-κb Inhibitorsmentioning
confidence: 99%
“…6 Glioma cell lines expressing dominant-negative p53 V135A were prepared as described. 7 All cell lines were maintained in Dulbecco's modified Eagle's medium (DMEM; GIBCO Life Technologies, Eggenstein, Germany) containing 10% fetal calf serum (FCS), glutamine (2 mM), penicillin (100 IU/ml)/ streptomycin (100 mg/ml) and the appropriate antibiotics. Hoechst 33258, propididum iodide (PI), uric acid, catalase and tiron (disodium-4,5-dihxydroxybenzene-1,3-disulphonate) were obtained from Sigma (Deisenhofen, Germany), dichlorodihydro-fluorescin-diacetate (H 2 DCFDA) and dihydroethidium (DHE) were from Molecular Probes (Leiden, Netherlands), zVAD-fmk (benzyloxycarbonylVal-Ala-DL-Asp-fluoromethylketone) from Bachem (Weil am Rhein, Germany).…”
Section: Methodsmentioning
confidence: 99%